Answer:
Hope this helps. If not let me know and I'll explain it better
Answer:
Step-by-step explanation:
Alternate forms:
x^2 + y (y + 4) = 5
x^2 + y^2 + 4 y - 5 = 0
Solutions:
y = -sqrt(9 - x^2) - 2
y = sqrt(9 - x^2) - 2
Integer solutions:
x = ± 3, y = -2
x = 0, y = -5
x = 0, y = 1
Implicit derivatives:
(dx(y))/(dy) = -(2 + y)/x
(dy(x))/(dx) = -x/(2 + y)
100.014. I think this is it
Answer:
Step-by-step explanation:
Remark
Choose any number at all and see what happens.
Suppose x = 8
3*(8 + 1) = 3*8 + 3
3(9) = 27
3*8 + 3 = 24 + 3 = 27
What you have shown is that the second choice is incorrect. There is at least one value that makes the equation correct (that is, both sides come to the same result.)
If choice two is false then choice one must be true since these results may give the only 2 possible results.